2011
DOI: 10.1002/jemt.21121
|View full text |Cite
|
Sign up to set email alerts
|

Differential nanofiller cluster formations in dental adhesive systems

Abstract: Nanofillers aggregation occurred in all adhesive systems in presence of additional solvents. In general, aggregate sizes were higher after the addition of ethanol. Formed clusters size values are always above the dimensions of the spaces existing between the demineralized collagen fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The polymerization of monomers was not hindered by the BG-Bi particles as no reaction with the particles is expected. Other studies have shown that this kind of particle does not hinder the hardening of endodontic sealing material, too [32]. Yet, these particles tend to cluster, most of the monomers are surrounded by other monomers and have therefore a similar probability of reaction as in the unfilled adhesive.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The polymerization of monomers was not hindered by the BG-Bi particles as no reaction with the particles is expected. Other studies have shown that this kind of particle does not hinder the hardening of endodontic sealing material, too [32]. Yet, these particles tend to cluster, most of the monomers are surrounded by other monomers and have therefore a similar probability of reaction as in the unfilled adhesive.…”
Section: Discussionmentioning
confidence: 92%
“…Considering the combination of all 3 investigated structural characteristics of the modified adhesive: degree of conversion, water sorption and sol fraction, the adhesive filled with POSS-8 particles exhibited improved properties when compared to the unfilled adhesive.All three studied particles in combination with the adhesive showed a bioactive behavior. Even though the bioactive glass is known and popular for its bioactive properties[4,17,[32][33][34][35], the bioactive characteristics of POSS particles have not been examined profoundly. The bioactivity of methacryl-functionalized POSS was proven in a single study where, mixed with polyethylene glycol, the particles induced the apatite formation on the composite surface after immersion in Dulbecco's phosphate buffered saline[21].…”
mentioning
confidence: 99%
“…With low percentages of filler, the adhesive resin might still infiltrate the collagen matrix, but as the percentage of filler increases, these wider filler particles, in conjunction with an increased adhesive viscosity, may accumulate on top of the collagen network impeding the infiltration of the resin into the collagen network resulting in a flawed hybrid layer. In addition, filler particles might precipitate and form clusters which may preclude even more the penetration of adhesive resin [9,22]. On the other hand, for same filler content, smaller particles increase the viscosity even more due to the increase in surface area [13] and therefore, particles may penetrate between the collagen fibers, but the higher viscosity may not allow a complete replacement of the demineralized dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, fillers may form clusters and further obstruct adhesive penetration within the collagen network [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…In Prime & Bond® NT™, acetone is used as a solvent rather than ethanol, as clustering potential of nano-fillers were found to increase on using ethanol as a solvent in dental adhesives (may reach 1.6µm or more). (35) Another reason that may clarify the higher bond strength of resin composite to TheraCal LC on using Prime & Bond® NT™ is the included di-and tri-methacrylate resin in Prime & Bond® NT™ adhesive. According to their functionality; the used cross-linking methacrylates can be either dimethacrylates, or multifunctional methacrylates.…”
Section: Discussionmentioning
confidence: 99%